Papel de las células dendríticas en la infección por el virus dengue: Blancos de replicación y respuesta inmune (2017)
Dengue fever, caused by dengue virus (DENV) infection, is one of the most important diseases in the world, not only due to the high morbidity/mortality rates it causes, but also because of its great economic and social impact in tropical/subtropical countries. DENV infection has a wide range of clinical manifestations ranging from asymptomatic infection or infection with mild symptoms to severe dengue that can lead to death. At present, no etiological treatment or effective globally distributed vaccine against the four DENV serotypes exists. Despite great efforts made to understand the mechanism associated with DENV disease pathogenesis the causes leading to severe dengue presentation have not been clarified. Some hypotheses seek to give a biological and physiological explanation to the clinical manifestations that appear during the infection. Based on the evidence that after contact with dendritic cells DENV alters the functionality of these cells, this review aims to describe the most relevant findings regarding the importance of dendritic cells in the context of DENV infection and progression of the illness. © 2017, Sociedad Chilena de Infectologia. All rights reserved.